Corrective Action and School Choice in NYC - Doug Hamman; E. Allen Schenck (Arizona State University, 2002)
Districts play a critical role in reforming schools. In January 2000, NYC community school districts applied for Title I, IASA, funding to carry out corrective actions against historically low-performing schools. Our purpose was to examine (a) how districts planned to take corrective action to address problems that cause low performance; and (b) the extent to which school choice could be implemented in those districts which were applying for corrective action funding. Districts most commonly identified teacher turnover, poor-quality instruction, and student needs as causes of low performance. In response, districts proposed providing professional development related to instructional strategies, but often ignored other important issues. Moreover, most districts described plans to take corrective actions that would decrease schools' decision-making authority, but then failed to identify steps to increase the districts' own capacity to execute greater responsibility once control had been taken from the schools. Districts overall seemed unable to implement school choice plans in an effective manner.